Carboxymethyl starch with high degree of substitution: synthesis, properties and application - Spychaj, T.; Zdanowicz, M.; Kujawa, J.; Schmidt, B. (Polimery, 2013)
Highly substituted (degree of substitution, DS about 0.9) carboxymethyl starch (CMS) was prepared in isopropanol/water suspension. The influence of etherification reaction parameters on DS, reaction efficiency, number average molar mass as well as the viscosity of 2 wt. % aqueous solution was determined. Using laser scanning microscopy, X-ray diffraction and infrared spectroscopy techniques allowed to evaluate the morphological changes of modified starch granules when compared to native starch ones. An attempt to apply CMS (of high and medium DS: 0.94 and 0.39, respectively) for flocculation or dispergation tests of selected aqueous suspensions [iron(II) sulphate, iron(III) oxide, iron(III) laurate and aluminosilicates: kaolinite and calcium montmorillonite] has been performed. In case of iron(II) sulphate and iron(III) oxide high substituted CMS exhibited effective flocculating properties. Moreover, it worked as a good dispersing agent for mineral aluminosilicate suspensions.